Physiotherapy in a Patient with Electric Burn from a Lightning Strike: Case Report - Pinzon Rios , Ivan Dario (2025)
Burns caused by an electric shock from lightning are an uncommon injury and can be very debilitating for the individual. This case describes a patient with an electric burn resulting from a lightning strike, whose physiotherapeutic evaluation and intervention were based on the guidelines provided by the American Physical Therapy Association (APTA), considering the four domains (cardiovascular/pulmonary, neuromuscular, musculoskeletal, and integumentary), to help achieve maximum functional independence. The physiotherapeutic rehabilitation process included 15 intervention sessions, during which the patient showed functional recovery in daily activities and an improved quality of life.